2020
DOI: 10.3389/fpsyg.2020.00657
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Enriched Sport Program on Children’s Executive Functions: The ESA Program

Abstract: The effects of physical exercise on executive functions (EFs) are welldocumented. EFs are involved in daily activities, and their development determines the quality of people's future life, both in terms of mental health and quality of life. The purpose of the current paper is to evaluate the effects of a physical education program, elaborated within the Enriched Sports Activity Program (ESA Program), an Erasmus + Project, on EFs, namely, visuospatial working memory, inhibitory control, cognitive flexibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
(65 reference statements)
2
20
1
1
Order By: Relevance
“…Detailed description of the study design and the ESA Program can be found elsewhere, describing both the cognitive tests and their administration and motor components, as well as the full description of the crunning test and administration procedures within the project [ 15 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed description of the study design and the ESA Program can be found elsewhere, describing both the cognitive tests and their administration and motor components, as well as the full description of the crunning test and administration procedures within the project [ 15 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, all testing procedures were performed in the same way and order. At the beginning of the project, each participant underwent a cognitive examination [ 29 ] and a physical evaluation [ 15 ], which were repeated at the end of the intervention. Before the start of the ESA training program, each participant also underwent a psychological test battery (ESA PTB, a 32 item questionnaire which includes questions regarding personal information, lifestyle-related factors and school-associated information), which was administered on two different occasions prior to the inclusion of the participants in the ESA program.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The program consisted of physical exercises that were modified to stimulate the three core executive functions, namely inhibitory control, working memory, and task shifting. ESA Program revealed to have positive effects on children's physical performance (Thomas et al, 2020) and executive functions (in particular, on working memory and task shifting) (Gentile et al, 2020).…”
Section: Introductionmentioning
confidence: 99%